MXene Enhanced 3D Needled Waste Denim Felt for High-Performance Flexible Supercapacitors - Fan, Wei; Wang, Qi; Rong, Kai; Shi, Yang; Peng, Wanxi; Li, Handong; Guo, Zhanhu; Xu, Ben Bin; Hou, Hua; Algadi, Hassan; Ge, Shengbo (Nano-Micro Letters, 2023)
MXene, a transition metal carbide/nitride, has been prominent as an ideal electrochemical active material for supercapacitors. However, the low MXene load limits its practical applications. As environmental concerns and sustainable development become more widely recognized, it is necessary to explore a greener and cleaner technology to recycle textile by-products such as cotton. The present study proposes an effective 3D fabrication method that uses MXene to fabricate waste denim felt into ultralight and flexible supercapacitors through needling and carbonization. The 3D structure provided more sites for loading MXene onto Z-directional fiber bundles, resulting in more efficient ion exchange between the electrolyte and electrodes. Furthermore, the carbonization process removed the specific adverse groups in MXenes, further improving the specific capacitance, energy density, power density and electrical conductivity of supercapacitors. The electrodes achieve a maximum specific capacitance of 1748.5 mF cm−2 and demonstrate remarkable cycling stability maintaining more than 94% after 15,000 galvanostatic charge/discharge cycles. Besides, the obtained supercapacitors present a maximum specific capacitance of 577.5 mF cm−2, energy density of 80.2 μWh cm−2 and power density of 3 mW cm−2, respectively. The resulting supercapacitors can be used to develop smart wearable power devices such as smartwatches, laying the foundation for a novel strategy of utilizing waste cotton in a high-quality manner. Highlights: 1 An ultralight and flexible supercapacitor is developed by an effective 3D fabrication method that uses MXene to fabricate waste denim felt through needling and carbonization. 2 The electrodes have a maximum specific capacitance of 1748.5 mF cm−2 and demonstrate remarkable cycling stability with more than 94% after 15,000 galvanostatic charge/discharge cycles 3 The loaded more MXene onto Z-directional fiber bundles results in enhanced specific capacitance, energy density and power density of supercapacitors.